PENGARUH KOMPENSASI DAN BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. DANA PURNA INVESTAMA KANTOR PUSAT JAKARTA - Febri Fikri Abdullah; M. Kausar Maulana (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2024)
To determine the effect of compensation and workload on employee job satisfaction of PT. Dana Purna Investama Jakarta Head Office. The population in this research are employees of PT. Dana Purna Investama Jakarta Head Office. This research uses multiple and simple linear regression test methods. Based on the test results together, it shows that compensation and workload have a positive and significant effect on employee job satisfaction at PT. Dana Purna Investama Jakarta Head Office. Meanwhile, the partial test of both compensation and workload has a significant effect on employee job satisfaction.